Authority Fragmentation Within Sentra Gakkumdu and Its Impact on The Effectiveness of Electoral Criminal Law Enforcement in Indonesia - La Radi Eno (Jurnal Smart Hukum (JSH), 2026)
The enforcement of electoral criminal offenses constitutes an integral component of the electoral justice system, serving to safeguard the integrity of electoral processes, protect citizens’ political rights, and strengthen democratic legitimacy based on the principles of justice, legal certainty, and political equality. However, the Integrated Law Enforcement Center (Sentra Gakkumdu), which consists of the General Election Supervisory Agency (Bawaslu), the Indonesian National Police, and the Public Prosecution Service, has not yet fully succeeded in establishing an integrated system for the enforcement of electoral criminal law. This study aims to analyze the factors contributing to the fragmentation of authority within Sentra Gakkumdu and to formulate an ideal institutional model for enhancing the effectiveness of electoral criminal law enforcement based on the principle of electoral justice. This research employs a normative legal research method using statutory, conceptual, and case approaches. Legal materials were analyzed qualitatively through descriptive-analytical and prescriptive methods to develop a legal framework relevant to the issues under examination. The findings reveal that the authority structure of Sentra Gakkumdu remains predominantly coordinative rather than integrative, resulting in fragmentation across normative, institutional, evidentiary, and decision-making dimensions. Such fragmentation has contributed to legal uncertainty, procedural inefficiencies, and the suboptimal enforcement of electoral criminal offenses. This study proposes the reconstruction of an Integrated Electoral Criminal Justice System (IECJS) that integrates supervisory, investigative, and prosecutorial functions through the harmonization of authority, the unification of evidentiary standards, and the establishment of an effective mechanism for resolving institutional conflicts. The proposed model is expected to enhance the effectiveness of electoral criminal law enforcement while promoting electoral justice and preserving democratic integrity in Indonesia.